Clinical imaging of primary pulmonary nucleoprotein of the testis carcinoma - Huang, Wenpeng; Zhang, Yongbai; Yang, Qi; Gao, Ge; Qiu, Yongkang; Li, Liming; Kang, Lei (Frontiers in Medicine, 2023)
Objective Primary pulmonary nucleoprotein of the testis (NUT) carcinoma is very rare in the clinic. In this study, the clinicopathological manifestations and imaging features of the primary pulmonary NUT carcinoma were investigated to improve the diagnosis of this disease. Methods Six patients with pathologically diagnosed pulmonary NUT carcinoma were analyzed, including three males and three females, aged 19–64 (49.00 ± 16.40) years, with clinical manifestations of cough in two cases, hoarseness in one case, blood in sputum in one case, chest pain in one case, and physical examination findings in one case, with a disease duration of 5 days to 4 months. The clinical and imaging data including CT and PET/CT were retrospectively analyzed. Further literature reviews were analyzed in both pulmonary and extrapulmonary NUT carcinoma cases who performed 18F-FDG PET/CT. Results Most of the patients with pulmonary NUT carcinomas presented as heterogeneous lobulated masses (83.33%), four cases (66.67%) were located in the upper lobe of the left lung, one case (16.67%) in the middle lobe of the right lung, and one case (16.67%) in the lower lobe of the right lung, with the maximum diameter ranging from 1.30 to 8.90 cm and the median of 3.55 cm, most of them were irregularly shaped, with more lobulated margins and more heterogeneous density (83.33%), and the enhancement was mild. PET/CT showed increased 18F-FDG uptake in the lesion and metastatic areas. Both the pulmonary NUT patients in this study and literature reviews showed the SUVmax of the tumor ranged from 5 to 40 with an average value of 12.8, whereas that of extrapulmonary lesions had a range of SUVmax at 4.5–64.1 and a mean of 13.8. Conclusion In patients with central lung masses, rapid disease progression, and poor response to initial treatment, the possibility of NUT cancer should be considered and anti-NUT monoclonal antibody immunohistochemical staining, combined with genetic detection, if necessary, should be performed as soon as possible. CT and PET/CT imaging are essential for the staging, management, treatment response assessment, and monitoring of pulmonary NUT cancer.